KONTRIBUSI BUDAYA, KEPEMIMPINAN, KEPUASAN KERJA, DAN KOMITMEN DALAM PENINGKATAN KINERJA DOSEN - Yusaini Yusaini (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
This study examines four factors that allegedly influence causality on the performance of lecturers in the State Islamic Religious College (PTKIN) in Aceh. So the purpose of this study is to find out whether or not there is a positive influence on organizational culture, job satisfaction, and organizational ommitment to the performance of PTKIN lecturers in Aceh province. The population in this study were all PNS lecturers in the PTKIN Aceh environment totaling 727 people and the sample was determined by the Slovin formula to be 258 people. The data collection instrument used a questionnaire composed of 154 questions that were previously tested for the validity and reliability of the instrument. Data analysis techniques used part analysis (path analysis) which was previously required to test requirements for analysis, such as tests of normality, linearity, homogeneity and correlation tests between variables. The results found that organizational culture, leadership, job satisfaction and organizational commitment directly influence the work performance of PTKIN lecturers in Aceh province. Keywords: Organizational culture, Leadership, Job Satisfaction, Organizational Commitment, Work performance